2018
DOI: 10.1136/bcr-2018-224320
|View full text |Cite
|
Sign up to set email alerts
|

Acinic cell carcinoma of the parotid gland in pregnancy: an approach to cancer in pregnancy

Abstract: A 27-year-old woman presented with an enlarging painless right preauricular mass at 28 weeks' pregnant. The mass had been stable for more than 10 years, but showed rapid growth during pregnancy. Imaging and biopsy were consistent with parotid gland malignancy, with surgical resection undertaken at 33+4 weeks' gestation. Histopathology confirmed acinic cell carcinoma. Labour was induced without complication at 36+6 weeks' gestation and adjuvant radiotherapy commenced 2 weeks postpartum. At 9 months follow-up, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…HNACC could be found at any age, and the mean age at diagnosis was 50 years. Previous research on HNACC is based on single institutional experiences, and because of the small sample size, those studies are often not sufficiently powerful to find considerable differences in survival that are related to general demographic parameters [11][12][13]. In the survival analysis in our study, significant differences in DSS and OS were found to be related to age range, mean age, gender, race and marital status (P < 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…HNACC could be found at any age, and the mean age at diagnosis was 50 years. Previous research on HNACC is based on single institutional experiences, and because of the small sample size, those studies are often not sufficiently powerful to find considerable differences in survival that are related to general demographic parameters [11][12][13]. In the survival analysis in our study, significant differences in DSS and OS were found to be related to age range, mean age, gender, race and marital status (P < 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…HNACC could be found at any age, and the mean age at diagnosis was 50 years. Previous research on HNACC is based on single institutional experiences, and because of the small sample size, those studies are often not su ciently powerful to nd considerable differences in survival that are related to general demographic parameters [11][12][13]. In the survival analysis in our study, signi cant differences in DSS and OS were found to be related to age range, mean age, gender, race and marital status (P < 0.001).…”
Section: Discussionmentioning
confidence: 53%
“…Since PAs occur more frequently in females than in males, with a female‐to‐male ratio of about 1.6:1, 2,3 it has been hypothesized that oestrogen may play a role in salivary tumour proliferation. While this has not been shown in laboratory studies, 4,5 various case reports describe rapid growth of parotid tumours during pregnancy 6,7 . For pregnant patients, it is possible that parotid tumours may have accelerated growth and therefore the potential for higher rates of surgical complexity.…”
Section: Introductionmentioning
confidence: 99%
“…laboratory studies, 4,5 various case reports describe rapid growth of parotid tumours during pregnancy. 6,7 For pregnant patients, it is possible that parotid tumours may have accelerated growth and therefore the potential for higher rates of surgical complexity. Whether this rapid growth indicates a possible malignant transformation is also questionable.…”
mentioning
confidence: 99%